2013
DOI: 10.1103/physrevd.88.054002
|View full text |Cite
|
Sign up to set email alerts
|

Parton densities from LHC vector boson production at small and large transverse momenta

Abstract: The parton densities of the proton are of fundamental importance not only for our description of hadronic and nuclear structure, but also for reliable predictions for new heavy-particle searches at colliders. At the large partonic momentum fractions required for the production of these particles, the parton distribution functions-in particular, that of the gluon-are unfortunately still badly constrained. In this paper, we investigate the possibility to improve on their determination with new data coming from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…In particular, very little is known about the gluon PDF in nuclei, which is, however, important to understand nuclear shadowing [8] and its possible relation to diffraction [9], saturation [10], and the initial condition for the creation of the quark-gluon plasma in heavy-ion collisions [11]. The situation could be somewhat improved by including pion production data from BNL RHIC [12], albeit at the cost of introducing a fragmentation function uncertainty, and recently also with the first electroweak boson [13] and in particular dijet [14] data from pPb collisions at the CERN LHC [15]. In addition, a recent reweighting study has shown also that forward heavy-quark and quarkonium production data from the CERN LHC have the potential to better constrain future analyses [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, very little is known about the gluon PDF in nuclei, which is, however, important to understand nuclear shadowing [8] and its possible relation to diffraction [9], saturation [10], and the initial condition for the creation of the quark-gluon plasma in heavy-ion collisions [11]. The situation could be somewhat improved by including pion production data from BNL RHIC [12], albeit at the cost of introducing a fragmentation function uncertainty, and recently also with the first electroweak boson [13] and in particular dijet [14] data from pPb collisions at the CERN LHC [15]. In addition, a recent reweighting study has shown also that forward heavy-quark and quarkonium production data from the CERN LHC have the potential to better constrain future analyses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this process dominates for inclusive Z production within a rapidity range of |y| < 2.1. However, already for Z transverse momenta around 25 GeV quark-gluon scattering qg → Zq is of similar size, and around p T = 100 GeV the latter process constitutes 80% of the total cross section [157]. For Z-boson transverse momenta of 180 GeV, parton-momentum fractions x 1/2 = (M/ √ s) exp(±y) of about x = 0.05 are probed.…”
Section: Differential Vector-boson Cross Sectionsmentioning
confidence: 97%
“…At the low p T (Z) region, p T (Z) < ∼ 20 GeV, the sub-process with initial state qq has significant contribution to the total cross section, while in the high p T (Z) region, p T (Z) > ∼ M Z /2, the sub-process gq becomes dominant (∼ 70 -80%). These relative sub-process contributions are also valid at the NLO accuracy [12,22,23]. Therefore, the inclusive Z boson production cross section is one of the potential measurement to probe the gluon density inside the proton at the LHC [24].…”
Section: Introduction 2 Inclusive Z Production At Lhcmentioning
confidence: 99%